FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN DAN DAMPAKNYA TERHADAP LOYALITAS PADA PEMBELIAN PRODUK ES TEH INDONESIA - Asfina Safa Maulida (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2025)
This research aims to evaluate the influence of store atmosphere, product quality, and halal labels on customer loyalty, as well as the mediating role of satisfaction among Indonesian Iced Tea customer on the island of Java. Quantitative methods were used in this research invloving five constructs, and the number of samples used was 253 respondents from Indonesian Iced Tea consumers on Java Island. The sampling technique used was purposive sampling. This research uses the PLS (Partial Least Square) analysis technique, using SmartPLS with inner model and outer model as well as bootstrapping. Testing the hypothesis that store atmosphere variables, product qualitu, and halal labels have a positive and significant effect on customer loyalty through customer satisfaction. The product quality variable has a positive and significant effect on customer loyalty. meanwhile, the store atmosphere and halal label variables do not have a significant effect on customer loyalty.